Analisis Potensi Kawasan Obyek Wisata Pantai Alam Indah Dan Pantai Purwahamba Indah Di Kota Tegal Jawa Tengah - Utami, Ditya Mita; , Drs. kuswaji Dwi Priyono,M.Si; , Dra. Hj. Umrotun,M.Si (2017)
Heritage is a place that has a beautiful and can be used as a place of entertainment for people who are on holiday in an effort to meet the spiritual needs and menunmbuhkan love of natural beauty. This study aims to determine the potential of the internal region and the external Alam Indah Beach attractions and Turkish Purwahamba Beautiful and know the direction of development potential Alam Indah Beach neighborhood and Turkish Purwahamba Indah. The method used is the analysis of the primary methods that are equipped with a field survey conducted to obtain data on the location of attractions and interviews with visitors and employees of the department of tourism which has a capacity of tourism managers, while managing data using scoring techniques. Results of research on get namely Alam Indah Beach attractions have a high internal potential, high external potential and the combined potential is high, whereas Purwahamba Indah Beach attractions have internal potential moderate, low external potential and the potential of being combined. Tutorial potential development Coast neighborhood Alam Indah will be the object of a better tour and will be directed into a tourist attraction provides a resort or cottage (inn) near the beach, as well as providing some miniature charm of the sea in order to increase the knowledge of children about marine wildlife, while Purwahamba Beach Beautiful objects add mangrove cultivation to avoid abrasion sea water and add outbound area to attract visitors in groups. Keywords: Potential Internal, External Potential, Potential Heritage.